Particle partitioning and geography drive divergent microbial assembly and network connectivity in coastal South China Sea - Pang, Shimei; Chen, Songze; Lin, Ziqiu; Xie, Wei; Xu, Yongqian; Zhang, Chuanlun (Frontiers in Microbiology, 2026)
A pronounced nutrient gradient spans from the eutrophic Pearl River Estuary (PRE) to the oligotrophic Northern South China Sea (NSCS), yet its influence on microbial community distribution and cross-domain interactions remains poorly understood. Here, we combined rRNA amplicon sequencing, cross-domain network analysis, and null model approaches to characterize and compare the community structure, assembly processes, and interactions of archaeal, bacterial, and eukaryotic communities in particle-attached (PA) and free-living (FL) fractions along the PRE-NSCS gradient. In the PRE, microbial community assembly was predominantly governed by stochastic processes, resulting in pronounced differences in potential connectivity predicted by null models. Notably, ammonia-oxidizing archaea associated with particles likely functioned as key connectors linking nitrification modules with heterotrophic clusters. In contrast, in the NSCS, cross-domain network analysis revealed that eukaryotes play a central role in maintaining inter-domain connectivity, while FL heterotrophic bacteria formed tightly coupled core networks with their autotrophic partners. Consistent with these patterns, validated topological structures indicated that PRE communities are dominated by stochastic processes (dispersal limitation and drift), whereas NSCS FL communities are primarily shaped by homogeneous selection. Collectively, these results demonstrate that geography and particle partitioning jointly regulate microbial community assembly and network connectivity, thereby influencing distinct microbial remineralization pathways associated with particulate versus dissolved organic matter, and providing new insights into carbon-nitrogen coupling in dynamic coastal ecosystems.